Methodology of Thermal Stress Determination in Continuous Welded Rail - Vnenk, Petr (Univerzita Pardubice, 2022)
This dissertation deals with the stress determination in continuous welded rail and proposes a methodology to determine the development of the neutral temperature. It summarizes the current knowledge in this field and presents results of the performed research. The performed research covers problems of the rail temperature determination, specifically the investigation into the impact of air temperature, cloudiness and geography on the rail temperature; and problems of the continuous welded rail neutral temperature development, specifically the continuous welded rail strain monitoring and the determination of the neutral temperature development.
Keywords: kolejnice; teplota; napětí; tenzometr; metodika; rail; temperature; stress; strain gauge; methodology